Inside the game - Zucker, Jonny (Stone Arch Books, 2007)
Aided by a girl they have never seen before, best friends Rex Jones, Dave, and Carl race for their lives when Rex's mysterious cell phone drops them into a computer game called Motor Speed Chase--or perhaps a more deadly version of that game.